Eco Friendly Synthesis and Structural Analysis of Ag2O/Ag Nanoparticles Derived from Hibiscus Sabdariffa Extract - Ali K. Hattab (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Nanotechnology enables the fabrication of novel materials with unique structural and optical properties, with silver oxide (Ag₂O) nanoparticles being of particular interest for catalytic, sensing, and optoelectronic applications. Specific Background: Conventional chemical synthesis of Ag₂O nanoparticles often involves toxic reagents and harsh conditions, posing environmental and biomedical limitations. Knowledge Gap: Despite advances in green chemistry, efficient, eco-friendly routes to control particle size, morphology, and stability of Ag₂O/Ag nanoparticles remain underexplored. Aims: This study develops an environmentally sustainable synthesis of Ag₂O/Ag nanoparticles using Hibiscus sabdariffa extract as a natural reducing and stabilizing agent. Results: X-ray diffraction confirmed a cubic crystal structure with an average crystallite size of 35.60 nm, while FESEM revealed irregular spherical particles averaging 57.2 nm. Energy-dispersive X-ray spectroscopy verified silver and oxygen elements, UV-Vis spectroscopy showed a 414 nm absorption peak with a 2.88 eV direct bandgap, and FTIR detected characteristic O–H, C–H, and Ag–O bonds. Novelty: This work demonstrates a cost-effective, plant-extract-based synthesis achieving precise structural and optical control without hazardous chemicals. Implications: The eco-friendly route supports scalable production of Ag₂O/Ag nanoparticles for applications in catalysis, biomedical devices, and optoelectronics, contributing to sustainable nanotechnology. Highlights: Plant extract acts as natural reducing and stabilizing agent. Nanoparticles show 2.88 eV direct bandgap with 414 nm absorption. Sustainable method enables scalable, non-toxic production. Keywords: Crystal, Silver, Spectrum, Nanoparticles, Bandgap